Water fluoridation in 40 Brazilian cities: 7 year analysis. - Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP]; Saliba, Orlando [UNESP]; Sumida, Doris Hissako [UNESP]; Souza, Neila Paula de; Chiba, Fernando Yamamoto; Garbin, Clea Adas Saliba [UNESP] (FapUNIFESP (SciELO), 2013)
Fluoride levels in the public water supplies of 40 Brazilian cities were analyzed and classified on the basis of risk/benefit balance. Samples were collected monthly over a seven-year period from three sites for each water supply source. The samples were analyzed in duplicate in the laboratory of the Center for Research in Public Health - UNESP using an ion analyzer coupled to a fluoride-specific electrode. A total of 19,533 samples were analyzed, of which 18,847 were artificially fluoridated and 686 were not artificially fluoridated. In samples from cities performing water fluoridation, 51.57% (n=9,720) had fluoride levels in the range of 0.55 to 0.84 mg F/L; 30.53% (n=5,754) were below 0.55 mg F/L and 17.90% (n=3,373) were above 0.84 mg F/L (maximum concentration=6.96 mg F/L). Most of the cities performing fluoridation that had a majority of samples with fluoride levels above the recommended parameter had deep wells and more than one source of water supply. There was some variability in the fluoride levels of samples from the same site and between collection sites in the same city. The majority of samples from cities performing fluoridation had fluoride levels within the range that provides the best combination of risks and benefits, minimizing the risk of dental fluorosis while preventing dental caries. The conduction of studies about water distribution systems is suggested in cities with high natural fluoride concentrations in order to optimize the use of natural fluoride for fluoridation costs and avoid the risk of dental fluorosis.
Keywords: fluoride; Brazil; city; dental caries; fluoridation; human; longitudinal study; public health; risk assessment; risk factor; statistics; time; tooth disease; Cities; Dental Caries; Fluoridation; Fluorides; Fluorosis, Dental; Humans; Longitudinal Studies; Public Health; Risk Assessment; Risk Factors; Time Factors